Решите уравнение:0.6х+7-0.5х-3=6.8

решите уравнение:0.6(х+7)-0.5(х-3)=6.8

     

    10.8-4=6.8

  • 0.6(x+7)-0.5(x-3)=6.8

     

    Ответ: x=11.

     

    0.6x+4.2-0.5x+1.5=6.8

    0.6x+4.2-0.5x+1.5=6.8

     

     

  •  

  •  

    x=11

    0.6(11+7)-0.5(11-3)=6.8

    0.6*18-0.5*8=6.8

    Проверка:

    0.6x+0.6*7-0.5x+0.5*3=6.8

    x=11

     

    0.6(x+7)-0.5(x-3)=6.8

    0.6x-0.5x=6.8-1.5-4.2

    6.8=6.8

     

     

     

     

    0.6x+4.2-0.5x-(-1.5)=6.8

     

     

     

    0.1x=1.1

     

    0.1x=1.1